Xinfeng capsule inhibits inflammation and oxidative stress in rheumatoid arthritis by up-regulating LINC00638 and activating Nrf2/HO-1 pathway. (30th January 2023) - Sun, Yanqiu; Liu, Jian; Xin, Ling; Wen, Jianting; Zhou, Qin; Chen, Xiaolu; Ding, Xiang; Zhang, Xianheng
Abstract: Ethnopharmacological relevance: Xinfeng capsule is a traditional Chinese medicine compound, which has been clinically used for more than 20 years in the treatment of rheumatoid arthritis (RA), ankylosing spondylitis, osteoarthritis and its extracurricular lesions. However, the molecular role of XFC in the treatment of RA remains unclear. Objective: This study aims to explore the efficacy and potential mechanism of XFC through retrospective data mining analysis, animal experiments and cell experiments. Methods: The effect of XFC on clinical laboratory indexes of RA patients was observed using data mining techniques combined with association rule analysis and a random walk model. Afterwards, a rat model of adjuvant arthritis (AA) was established with Freund's complete adjuvant, followed by the observation of pathological changes in synovial tissues and the ultrastructure of synoviocytes. A RA cell model was constructed by inducing fibroblast-like synoviocytes (FLSs) with tumor necrosis factor-alpha (TNF-α) to assess the effects of XFC-containing serum on inflammation and oxidative stress through long non-coding RNA LINC00638. Results: In retrospective data mining, XFC effectively reduced immune inflammation and increase the level of antioxidant enzymes in RA patients. Subsequently, animal experiments showed that XFC significantly repressed immune inflammation, oxidative stress, synovial hyperplasia, and cartilage destruction, while improving the ultrastructure of synoviocytes in AA rats. XFC-containing serum diminished the proliferation of TNF-α-induced RA-FLSs, increased LINC00638 expression ( P ＜0.01), decreased interleukin-6 (IL-6), IL-17, reactive oxygen species (ROS) and reactive nitrogen species (RNS) levels ( P ＜0.01), and increased the protein expression of nuclear factor erythrocyte 2-related factor 2 (Nrf2), heme oxygenase 1 (HO-1), and superoxide dismutase 2 (SOD2) ( P ＜0.01). Furthermore, rescue experiments manifested that XFC-containing serum reversed the effects of silencing LINC00638 on inflammation and oxidative stress in RA-FLSs. Conclusion: XFC inhibits inflammation and oxidative stress in RA by up-regulating LINC00638 and activating Nrf2/HO-1 pathway. Graphical abstract: Image 1